Palmitoylation of human FasL modulates its cell death-inducing function - Guardiola-Serrano, F (Nature Publishing Group, 2010)
Fas ligand (FasL) is a transmembrane protein that regulates cell death in Fas-bearing cells. FasL-mediated cell death is essential for immune system homeostasis and the elimination of viral or transformed cells. Because of its potent cytotoxic activity, FasL expression at the cell surface is tightly regulated, for example, via processing by ADAM10 and SPPL2a generating soluble FasL and the intracellular fragments APL (ADAM10-processed FasL form) and SPA (SPPL2a-processed APL). In this study, we report that FasL processing by ADAM10 counteracts Fas-mediated cell death and is strictly regulated by membrane localization, interactions and modifications of FasL. According to our observations, FasL processing occurs preferentially within cholesterol and sphingolipid-rich nanodomains (rafts) where efficient Fas–FasL contact occurs, Fas receptor and FasL interaction is also required for efficient FasL processing, and FasL palmitoylation, which occurs within its transmembrane domain, is critical for efficient FasL-mediated killing and FasL processing.